The Social and Public Health Impacts that Occurred in Rantau Utara Subdistrict after the Publication of the Labuhanbatu District Regulations No. 10 of 2011 About the Swallow Bird Tax, Indonesia - Nanda Aulia Yusuf Purba; Humaizi; Kariono (Britain International for Academic Research (BIAR) Publisher, 2019)
This study aim to find out the social and public health impact that occurred in rantau utara subdistrict after the publication of Labuhanbatu district regulations about the swallow bird tax. The method of this study is qualitative research by using interview data to local government and society. The result of this study there has been no social impact found in the District of Rantau Utara and Rantau Selatan Subdistrict Labuhanbatu Regency since Regional Regulation Number 10 of 2011 concerning Taxes for Swallow Bird Nests imposed.